Traditional medicinal plants as anticancer agents from Chhattishgarh, India: An overview - Ritesh Jain,; Sanmati K. Jain, (International Journal of Phytomedicine, 2010)
An attempt has been made to review some medicinal plants used for the prevention and treatment of cancer in Chhattisgarh. Information on the name of plants, family, parts used and method of preparation has been collected from Ethanobotanical literatures. Information collected has revealed 53 plants species that are used for treatment of cancer in Chhattisgarh. All these plants were further reviewed for scientific evidence, 33 plants out of 53 plants were found for possess anticancer, cytotoxic or antioxidant activity in various preclinical or clinical studies.